Correction: Modelling and prediction of the thermophysical properties of aqueous mixtures of choline geranate and geranic acid (CAGE) using SAFT-γ Mie. Issue 33 (22nd May 2020) - Di Lecce, Silvia; Lazarou, Georgia; Khalit, Siti H.; Pugh, David; Adjiman, Claire S.; Jackson, George; Galindo, Amparo; McQueen, Lisa
Abstract : Correction for 'Modelling and prediction of the thermophysical properties of aqueous mixtures of choline geranate and geranic acid (CAGE) using SAFT-γ Mie' by Silvia Di Lecce et al., RSC Adv., 2019, 9, 38017–38031. DOI: ; 10.1039/C9RA07057E